Presentation Accommodation Strategies and Academic Performance of Pupils with Visual Impairments in Inclusive Primary Schools in Bamenda-Cameroon - Nabi, Yigha Comfort; Wiysahnyuy, Lilian F.; Chu, Ambei Moses (Journal of Research in Innovative Teaching and Inclusive Learning, 2025)
This study examines the effectiveness of presentation accommodations on the academic performance of pupils with visual impairments in Bamenda City. The study specifically aimed at investigating the impact of Braille, large print, tactile materials and audio materials on the academic performance of pupils with visual impairments. The research design used in this study was a quasi experiment. A purposive sampling technique was used to select 20 pupils with visual impairments (11 partially sighted and 9 totally blind) and ten (10) teachers of pupils with visual impairments from Cameroon Baptist Convention (CBC) Primary School Nkwen and Inclusive Government Practicing School (IGPS) Nibung. The twenty pupils were randomly assigned to control and experimental groups. The experimental group received lessons in English Language and Environmental education through presentation accommodations while the control group did not receive such support. The intervention phase of the study took six weeks comprising a total of thirteen sessions: one session for the pre test, twelve instructional sessions and one final session for the post test. Quantitative data were analyzed using descriptive statistics (means and standard deviations) and t-tests, while qualitative data were thematically analyzed with direct quotations from participants. Findings showed that presentation accommodations significantly improved comprehension, participation, and academic performance. Pupils in the experimental group had a mean post-test score of 13.68 ± 0.338 compared to 8.61 ± 0.398 in the control group, with a mean difference of 5.07 (t = 9.842, p < 0.001). The correlation value at pretest level was weak (0.269), but strong at posttest level (0.681), indicating that presentation accommodation strategies have a strong and positive effect on the academic performance of pupils with visual impairment. Therefore teachers in inclusive classrooms should consistently use these presentation modes to foster equitable learning. There is also need for teachers to engage in professional development activities in this section.